Exploration of the Potential Geosite of Ijen Geopark Bondowoso Region as an Educational Tourism - Fuad Hasan; Intan Hayun Ningrum (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2023)
Geosite is one of the Ijen Geopark geosites in the Bondowoso region which has an initial design as a tourist destination which in its management only implements elements of tourism. Then after the Ijen Geopark was designated as a National Geopark and proposed to become part of the UNESCO Global Geopark (UGG), the status of the Wurung Crater, which was originally a destination, changed to a Geological Heritage Site (Geosite). This status change in its adjustment in the field with the concept of educational tourism is still not maximized. Geosite management needs to implement elements of tourism, science and education. The management concept is considered in accordance with the concept of educational tourism which includes tourism and educational activities. So the purpose of this research is to find out what potential the Wurung Crater geosite has so that it can meet the educational tourism indicators which consist of tutorial learning and field exploration. This research use descriptive quantitative research design and using survey/questionnaire methods and documentation studies in collecting data. The results of data analysis using descriptive percentages obtained a tutorial learning indicator value of 67.5% which was included in the "moderate" category and the field exploration indicator obtained a value of 75.8% in the "high" category. This shows that the Wurung Crater Geosite is superior in the preparation and provision of techniques, facilities, and learning media to support field exploration activities than in the provision of guide/interpreter facilities as well as the quality and quantity of guides/interpreters. But overall it can be concluded that the Wurung Crater Geosite has the potential for educational tourism which is included in the "high" category with the acquisition of an accumulated value of two indicators of 72.3%.